MLN2238 exerts its anti-tumor effects via regulating ROS/JNK/mitochondrial signaling pathways in intrahepatic cholangiocarcinoma - Xu, Hao; Xu, Guangyu; Xu, Qianhui; Xu, Chang; Zhou, Xiaohu; Bai, Yang; Yin, Lu; Ding, Yuan; Wang, Weilin (Frontiers in Pharmacology, 2022)
Background: Cholangiocarcinoma (CCA) is a highly malignant tumor with limited treatment options that contributes largely to cancer-related deaths worldwide. Compared with traditional transcriptomic analysis, single-cell RNA sequencing (scRNA-seq) is emerging as a more advanced and popular tool for the in-depth exploration of cellular diversity and molecular complexity. As a next-generation proteasome inhibitor, MLN2238 presents better pharmacodynamics, pharmacokinetics, and therapeutic responses in various cancers. However, its effects and mechanisms of action in CCA remain unknown. Methods: CCA tumor heterogeneity was determined based on 4239 qualified scRNA-seq data from 10 CCA samples. The potential biological roles of proteasome-related genes in CCA were investigated using a pseudo-trajectory reconstruction. The effect of MLN2238 on CCA cell proliferation was estimated using the CCK-8, EdU, and clone formation assays. Flow cytometry was used to examine the effect of added MLN2238 on cell cycle and apoptosis levels. Autophagic flux was detected using AdPlus-mCherry-GFP-LC3B cells. ROS levels and mitochondrial membrane potential were determined using DCFH-DA probing and JC-1 staining. JNK activation and mitochondrial apoptosis were observed using western blotting and immunofluorescence microscopy, respectively. Finally, we used a tumor-bearing mouse model to validate its efficacy in vivo for CCA treatment. Results: Proteasome-related genes were dysregulated in CCA progression and expressed at higher levels in tumor tissues. MLN2238 suppressed cell proliferation, blocked the cell cycle in the G2/M phase, promoted apoptosis, and induced cytoprotective autophagy in CCA cells. Furthermore, MLN2238 increased ROS levels and activated the JNK signaling pathway. Inhibition of ROS and JNK activation by NAC and SP600125 significantly reversed MLN2238-induced apoptosis. MLN2238 also suppressed the growth of CCA tumors in vivo. Conclusion: Proteasome-related genes play pivotal roles in CCA development. MLN2238, as a proteasome inhibitor, induces apoptosis in CCA cells through ROS/JNK/mitochondrial signaling pathways, and hence, making MLN2238 a potential therapeutic choice for CCA.